Psychologiczne kompetencje nauczycieli w świetle wybranych trudności uczniów szkół muzycznych = Psychological competences of teachers in the light of selected students' difficulties music schools - Nogaj, Anna Antonina (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article focuses on the psychological competences of teachers-artists working with children, youth, as well as students of music schools and universities. Psychological competences are presented in the context of a wide range of didactic and specialist competences. Their possession and development is a factor conditioning the capability, efficiency, and correctness in executing an optimal teacher-student relation, and in the case of artistic education the master-student relation. The psychological competences of teachers-artists require transformations due to the student's developmental stage, as well as due to the individual needs and capabilities of students.
Keywords: nauczyciele; kompetencje; psychologia; pomoc; uczeń; rozwój; teacher; competencies; psychology; support; students; development